Glutathione peroxidase activity and expression levels are significantly increased in acute coronary syndromes. (15th March 2017) - Holley, Ana; Pitman, Janet; Miller, John; Harding, Scott; Larsen, Peter
Abstract : High levels of the antioxidant enzyme, glutathione peroxidase (GPx), have been associated with improved outcomes following acute coronary syndromes (ACS), suggesting a protective role. How GPx levels are altered with coronary disease is not clearly established. This study examined GPx activity, protein, and mRNA levels in healthy controls, patients with stable coronary artery disease (CAD), and patients with ACS. We studied 20 individuals from each of the healthy control, stable CAD, and ACS groups. GPx activity and protein levels, along with oxidized low-density lipoprotein (oxLDL) were assayed in plasma. GPx mRNA levels from whole blood were quantified using real-time PCR. Levels of GPx activity in the plasma were higher in ACS (109±7.7 U/mL) compared with patients with stable CAD (95.2±16.4 U/mL, p<0.01) and healthy controls (87.6±8.3 U/mL, p<0.001). Plasma GPx protein levels were also elevated in ACS (21.6±9.5 µg/mL) compared with patients with stable CAD (16.5±2.8 µg/mL, p<0.05) and healthy controls (16.3±5.3 µg/mL, p<0.05). Levels of GPX1, GPX3, and GPX4 mRNA were significantly higher in the patients with ACS. Levels of oxLDL were also significantly higher in patients with ACS (61.9±22.2 U/L) than in patients with stable CAD (47.8±10.4 U/L, p<0.05) and healthy controls (48.9±11.9 U/L, p<0.05). Levels of oxLDL, GPx activity, protein, and mRNA are all significantly higher in patients with ACS compared with patients with stable CAD and healthy controls. These findings suggest that GPx may be upregulated in response to a change in oxidative stress during an ACS.